MEMBANGKITKAN KOMPETENSI IR 4.0. PADA GURU SEKOLAH DASAR MELALUI PELATIHAN SINGKAT PEMANFAATAN DIGITAL - Astri Dwi Jayanti S. (LPPM Universitas Terbuka, 2019)
The digital age drives change in many sectors of life. In this age, correspondence between two continents happens immediately, and knowledge is exchanged and expended rapidly. Teachers as a focal figure in the realm of instruction are required to redress and even decipher these progressions as a methods for facilitating students to secure the 21st century capabilities. In any case, actually, a large number of teachers are hesitant to connect with these changes, particularly those related with the utilization of innovation in instruction and learning. In some developing countries, for example, Indonesia, a great deal of teachers are frustrated with the digital gap, less expertise in applying technology, limited supporting infrastructure, and students’ age variation. This article investigates the impact of short training on digital technology use in education to 29 primary teachers in Jakarta, Indonesia. The training course includes the introduction of the materials on digital learning, followed by assignment of looking for learning resources on the web, and an essay writing as the assessment to finish of the program. The observations and interviews with 7 respondents showed that the activity of the training improved the teachers’ digital literacy, especially in the utilization of technology in education. Era digital menyebabkan perubahan yang signifikan disetiap lini kehidupan. Pada masa ini komunikasi antar dua benua terjadi seketika, realitas dimodifikasi dan dikonsumsi secara cepat. Guru sebagai sosok sentral dalam dunia pendidikan dituntut untuk mengimbangi bahkan menerjemahkan perubahan tersebut sebagai sarana menghasilkan peserta didik yang memiliki kompetensi abad 21. Namun pada kenyataanya banyak guru yang segan bersinggungan dengan perubahan ini, khususnya yang berkaitan dengan pemanfaatan teknologi dalam pembelajaran. Di beberapa Negara berkembang seperti Indonesia banyak guru yang frustasi karena adanya jurang digital yakni kurang terampil dalam mangaplikasikan teknologi, terbatasnya sarana-prasarana yang mendukung, dan adanya perbedaan usia dengan para peserta didik. Artikel ini mengeksplorasi implikasi dari pelatihan dan pengembangan keterampilan menggunakan teknologi digital yang diberikan kepada 29 guru sekolah dasar di Jakarta, Indonesia. Pelatihan dilaksanakan selama 2 hari pada bulan Juni 2019, diawali dengan penyajian materi, praktik mencari sumber pembelajaran melalui internet kemudian dilanjutkan dengan pemberian evaluasi berupa soal uraian. Berdasarkan hasil observasi dan wawancara dengan 7 orang guru diketahui bahwa pelatihan yang diberikan berdayaguna dalam meningkatkan literasi digital guru untuk memanfaatkan teknologi dalam pendidikan.